Use of Remote Sensing Data to Study the Aral Sea Basin in Central Asia—Geoscience and Geological Hazards - Deroin, Jean-Paul (Remote sensing (Basel, Switzerland), 2025)
The Aral Sea Basin (ASB), situated in Central Asia, serves as a prime example of a man-made environmental disaster. The practice of irrigation can be traced back to ancient times. However, the substantial water withdrawals that have occurred since the second half of the 20th century appear to have led to the irreversible drying up of the Aral Sea and the disruption of the flow of the Amu Darya and Syr Darya rivers. This study conducts a comprehensive review of satellite data from the past sixty years, drawing upon a selection of peer-reviewed papers available on Scopus. The selection of papers is conducted in accordance with a methodology that is predicated on the combination of keywords. The study focuses on geoscientific aspects, including the atmosphere, water resources, geology, and geological hazards. The primary sensors employed in this study were Terra-MODIS, NOAA-AVHRR, and the Landsat series. It is evident that certain data types, including radar data, US or Soviet archives, and very-high-resolution data such as OrbView-3, have seen minimal utilisation. Despite the restricted application of remote sensing data in publications addressing the ASB, remote sensing data offer a substantial repository for monitoring the desiccation of the Aral Sea, once the fourth largest continental body of water, and for the estimation of its water surface and volume. Nevertheless, the utilisation of remote sensing in publications concerning the Aral region remains limited, with less than 10% of publications employing this method. Sentinel-2 data has been utilised to illustrate the construction of the Qosh Tepa Canal in Afghanistan, a project which has been the subject of significant controversy, with a particular focus on the issue of water leakage. This predicament is indicative of the broader challenges confronting the region with regard to water management in the context of climate change. A comparison of the Aral Sea’s case history is drawn with analogous examples worldwide, including Lake Urmia, the Great Salt Lake, and, arguably more problematically, the Caspian Sea.